2020
DOI: 10.1109/ojpel.2020.3040628
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Type-III Turbine Impedance Models Including DC Bus Dynamics

Abstract: Several small-signal impedance models have been reported for type-III wind turbines for use in impedance-based system stability studies. Common to these models is the assumption that the dc bus between the rotor-and stator-side converters is an ideal voltage source. Under this assumption, there is no dynamic coupling between the two converters and the turbine can be represented by the impedance of the stator-side converter in parallel with the impedance of the induction generator with the rotor-side converter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This in turn causes a current response at both 𝑠 and 𝑠 − 𝑗2𝜔 at the ac terminal of the converter connected to node đ‘„ . The phenomenon is similar to the coupling between the rotor-and stator-side converters in a type-III turbine that was modeled in [33]. To account for it in the converter models ( 5) and ( 6), the transfer function from 𝑣 (𝑠) to 𝑖 (𝑠) and 𝑖 (𝑠 − 𝑗2𝜔 ) has to be included as the {𝑖, 𝑗} element of admittance matrix 𝐘 (𝑠) and 𝐘 (𝑠), respectively.…”
Section: Frequency-domain Modeling By Nodal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn causes a current response at both 𝑠 and 𝑠 − 𝑗2𝜔 at the ac terminal of the converter connected to node đ‘„ . The phenomenon is similar to the coupling between the rotor-and stator-side converters in a type-III turbine that was modeled in [33]. To account for it in the converter models ( 5) and ( 6), the transfer function from 𝑣 (𝑠) to 𝑖 (𝑠) and 𝑖 (𝑠 − 𝑗2𝜔 ) has to be included as the {𝑖, 𝑗} element of admittance matrix 𝐘 (𝑠) and 𝐘 (𝑠), respectively.…”
Section: Frequency-domain Modeling By Nodal Analysismentioning
confidence: 99%
“…To apply the system models developed in Secion IV, the grid impedance together with the transmission network is characterized by impedances measured at these two points according to (34)- (36). Since the grid is symmetrical and passive, it suffices to model its 𝐙 defined by (33). This is a symmetrical 2 × 2 matrix and is characterized by using the distributed tranmission-line model parameters given in Table 1.…”
Section: A Grid-following Converters With Couplingmentioning
confidence: 99%
“…One purpose of this section is to develop these models by combining the methods and models presented in the last two sections. Since type-III turbines have been treated in a separate work [27], the focus here will be type-IV turbines.…”
Section: Stability Of Wind Turbines and Wind Farmsmentioning
confidence: 99%
“…Of the two types of coupling, the first type affects individual turbine impedances but does not change the aggregation method. The method presented in the previous subsection for type-IV turbines and in [27] for type-III turbines allows individual turbine models to be developed to include the first type of coupling. For the purpose of this section, we assume these models have been developed and denote them as , , and , as defined in Subsection II.A, without regard for the type of the turbine.…”
Section: B Farm Impedance Modeling By Aggregationmentioning
confidence: 99%
“…However, it has been reported that the PLL used for grid synchronization may bring a significant impact on the stability, especially under the weak grid condition [29]. Although, the power synchronization control strategy on the RSC of DFIG system can improve the stability of the system, but ignoring the GSC and its PLL to study the system stability under weak grid may lead to inaccurate analysis [30].…”
Section: Introductionmentioning
confidence: 99%